Prevalence of breastfeeding and associated factors - The ALMAT study - Barge, Sílvio (2011)
PREVALENCE OF BREASTFEEDING AND ASSOCIATED FACTORS - ALMAT STUDY Objective: To determine the prevalence of breastfeeding at 6 months of age and to determine if the early cessation of breastfeeding is associated with maternal age, parity, education, employment status, smoking, alcohol consumption and knowledge of the benefits of breastfeeding. Study Type: Cross-sectional study. Location: USF Mais Saúde and USF Lethes, Local Health Unit of Alto Minho. Population:Women giving birth in 2009 in these regions. Methods: Between September 1 and October 15, 2010, we conducted telephone interviews with 163 mothers (106 from USF Lethes and 57 from USF Mais Saúde) selected from a list of the women giving birth in 2009 identified in the electronic medical record. The information was gathered using a questionnaire developed by the authors. The data collected were analyzed using descriptive and inferential statistics. Results: The prevalence of breastfeeding at 6 months was 36% (29% - 43%, CI 95%). The mean duration of breastfeeding was 5 months. The prevalence of breastfeeding was higher in older women. The prevalence of breastfeeding was high in women in lowest and highest level of education. It was lower in women who attended birth preparation classes. In a multivariate analysis, age was found to be a confounding variable, so these variables (education and pre-natal classes) were found not to be associated with breastfeeding. Conclusions: The prevalence of breastfeeding at 6 months of age in this population was found to be similar to that found in other studies, but lower than the goal by set by the World Health Organization. The association between breastfeeding and age is similar to that found in the literature. We believe that this study contributes to our knowledge of the factors associated with the prevalence of breastfeeding at 6 months of age in Portugal.